Final answer:
The expression Z - Y - X calculated using the values x = -1/3, y = 12/5, and z = -2 yields a result of -56/15.
Step-by-step explanation:
To solve for Z - Y - X using x = -1/3, y = 12/5, and z = -2, we can simply substitute the values into the expression:
- Z is replaced by -2.
- Y is replaced by 12/5.
- X is replaced by -1/3.
The expression becomes: (-2) - (12/5) - (-1/3).
Now, calculate:
-2 - 12/5 + 1/3 = (-2)(15/15) - (12/5)(3/3) + (1/3)(5/5)
Now combine the terms:
-30/15 - 36/15 + 5/15 = -61/15 + 5/15
-56/15
So, Z - Y - X = -56/15 when substituting the given values for x, y, and z.